The Effect of Race and Shear Stress on CRP-Induced Responses in Endothelial Cells. (2nd December 2021) - Ling, Chenyi; Cook, Marc D.; Grimm, Heather; Aldokhayyil, Maitha; Gomez, Dulce; Brown, Michael
Abstract : Background . C-reactive protein (CRP) is an independent biomarker of systemic inflammation and a predictor of future cardiovascular disease (CVD). More than just a pure bystander, CRP directly interacts with endothelial cells to decrease endothelial nitric oxide synthase (eNOS) expression and bioactivity, decrease nitric oxide (NO) production, and increase the release of vasoconstrictors and adhesion molecules. Race is significantly associated with CRP levels and CVD risks. With aerobic exercise, the vessel wall is exposed to chronic high laminar shear stress (HiLSS) that shifts the endothelium phenotype towards an anti-inflammatory, antioxidant, antiapoptotic, and antiproliferative environment. Thus, the purpose of this study was to assess the racial differences concerning the CRP-induced effects in endothelial cells and the potential role of HiLSS in mitigating these differences. Methods . Human umbilical vein endothelial cells (HUVECs) from four African American (AA) and four Caucasian (CA) donors were cultured and incubated under the following conditions: (1) static control, (2) CRP (10  μ g/mL, 24 hours), (3) CRP receptor (Fc γ RIIB) inhibitor followed by CRP stimulation, (4) HiLSS (20 dyne/cm 2, 24 hours), and (5) HiLSS followed by CRP stimulation. Results . AA HUVECs had significantly higher Fc γ RIIB receptor expression under both basal and CRP incubation conditions. Blocking Fc γ RIIB receptor significantly attenuated the CRP-induced decrements in eNOS expression only in AA HUVECs. Finally, HiLSS significantly counteracted CRP-induced effects. Conclusion . Understanding potential racial differences in endothelial function is important to improve CVD prevention. Our results shed light on Fc γ RIIB receptor as a potential contributor to racial differences in endothelial function in AA.